Cost‐Effectiveness of Nutrition Intervention in Long‐Term Care. Issue 11 (27th October 2015) - Simmons, Sandra F.; Keeler, Emmett; An, Ruopeng; Liu, Xulei; Shotwell, Matthew S.; Kuertz, Brittany; Silver, Heidi J.; Schnelle, John F.
Abstract : Objectives: To determine the cost‐effectiveness of two nutrition interventions on food, beverage, and supplement intake and body weight. Design: Randomized, controlled trial. Setting: Five skilled nursing home facilities. Participants: Long‐stay residents with orders for nutrition supplementation (N = 154). Intervention: Participants were randomized into a usual care control group, an oral liquid nutrition supplement (ONS) intervention group, or a snack intervention group. Research staff provided ONS, according to orders or a variety of snack foods and beverages twice per day between meals, 5 days per week for 24 weeks and assistance to promote consumption. Measurements: Research staff independently weighed residents at baseline and monthly during the 24‐week intervention. Resident food, beverage and supplement intake and the amount of staff time spent providing assistance were assessed for 2 days at baseline and 2 days per month during the intervention using standardized observation and weighed intake procedures. Results: The ONS intervention group took in an average of 265 calories more per day and the snack intervention group an average of 303 calories more per day than the control group. Staff time required to provide each intervention averaged 11 and 14 minutes per person per offer for ONS and snacks, respectively, and 3 minutes for usual care. Both interventions were cost‐effective in increasing caloric intake, but neither intervention had a significant effect on body weight, despite positive trends. Conclusion: Oral liquid nutrition supplements and snack offers were efficacious in promoting caloric intake when coupled with assistance to promote consumption and a variety of options, but neither intervention resulted in significant weight gain.